Design, analysis and fabrication of UTM hydraulic ram pump for water supply in remote areas - Sarip, S. (Institute of Advanced Engineering and Science, 2019)
This paper focuses on design, analysis and fabrication of hydraulic ram pump, which uses the force of gravity to deliver water to higher altitudes. It does not depend on electrical and fossil energy and robust, inexpensive, easy to install and maintain. All these qualities make it suitable for use in remote areas where water and electricity supply, especially in developing countries. The aim of this study is to construct a low cost UTM hydraulic ram pump for water supply in remote areas, provided that it must have a reliable design and made of materials available locally in Malaysia. The design must also be easy to assemble and dismantle, easy to maintain and durable with a long service life. In order to achieve these objectives, existing ram pump designs by other researchers were studied to provide the basics in designing the UTM hydraulic ram pump. The ram pump efficiency is 62%, based on drive pipe diameter of 3” and air chamber volume of 33.3 L. Referring to the guidelines and experimental data these design specifications allow a total of 7000 L/day (4.86 L/min) of water to be delivered to the storage tank. The power required is about 23.9 kW which is enough to overcome head losses of about 54.52 m. Through a test stand, the value of circulations is 49 cycle/minute and thus the overall performance of the ram pump can be calculated before installation in remote areas. Other factors such as the proper material selection and safety considerations were also prioritized.